International Financial Reporting Standard's (IFRS) Adoption in Ghana: Rationale, Benefits and Challenges - Adwoa Acheampomaa Boateng; Andrew Bissue Arhin; Valarie Afful (Centre for Behaviour and Wellness Advocacy, 2014)
The International Financial Reporting Standards (IFRS) was adopted by Ghana in 2007. The study assessed eighteen (18) professional accountants from listed firms on the Ghana Stock Exchange (GSE), to measure the benefits and challenges of IFRS. The study revealed that IFRS improved the access of local companies to international markets. It was also observed that the local firms gained more credibility, transparency, acceptance and consolidation following its adoption. However, most respondents believed that decreasing information cost, competitive leading edge, and integration of accounting Information Technology system were not major benefits as proposed by literature. Nonetheless, some of these local companies after the migration faced challenges like coping with the sophistication of the new standard, lack of qualified personnel, and additional operational cost. Nevertheless, most of the respondents disagreed with the proposition that IFRS had a negative impact on their firms' balance of retained earnings.